An Estimation Model for Hydraulic Conductivity of Low-Permeability and Unfilled Fractured Granite in Underground Water-Sealed Storage Caverns - Yangbing Cao; Weiguo Gong; Xiangxiang Zhang; Junxi Chen; Zhenping Huang (Geofluids)
The permeability of rock mass is closely related to the stability and safety of underground structure, especially in underground water-sealed storage caverns. With regard to the estimation approaches in predicting the hydraulic conductivity of fractured granite in water-sealed storage caverns, there are some limitations of parameter selection leading to poor applicability. Focusing on the contribution of the water conduction fractures (WCF) to the hydraulic conductivity, we attempted to propose a novel model, the CA model, for estimating its hydraulic conductivity based on the fracture orientation index and the normal stress index by analyzing the borehole wall imaging results and borehole water-pressure test results in the site of underground water-sealed storage caverns. The results indicated that the proposed model is suitable for low-permeability and unfilled fractured granite, exhibiting good effectiveness by clarifying the relation between geomechanical parameters and hydraulic behavior. Further, the parameters upon which the proposed model is based are representative and easy to obtain, which has certain guiding significance and reference value for analyzing the permeability characteristics of similar rock masses.